Effects of dried okra extract on lipid profile, renal function and some RAGE-related inflammatory genes expression in patients with diabetic nephropathy: A randomized controlled trial - Nazgol Bahreini; Maryam Saghafi-Asl; Omid Nikpayam; Ehsan Safaei; Vahideh Sadra; Laleh Fakhr; Hanieh Beyrampour-Basmenj; Parina Asgharian; Mohammad Asghari- Jafarabadi (Complementary Therapies in Medicine, 2024)
Background: Diabetic nephropathy (DN) is a common complication of type 2 diabetes. Okra (Abelmoschus esculentus L) is reported to have anti-diabetic effects. The present study aimed to investigate the effects of dried okra extract (DOE) supplementation on lipid profile, renal function indices, and expression of inflammatory genes, as well as serum level of soluble Receptor for Advanced glycation end products (sRAGE) in patients with DN. Methods: In this triple-blind randomized placebo-controlled clinical trial, 64 eligible patients with DN received either 125 mg of DOE or placebo daily along with DN-related nutritional recommendations for 10 weeks. Changes in kidney indices including proteinuria and estimated glomerular filtration rate (eGFR), lipid profile, serum SRAGE, as well as the expression of RAGE, ICAM-1, and IL-1 genes were measured over 10 weeks. Results: After adjustment for the potential confounders, between-group analyses showed no significant differences in terms of lipid profile, kidney function indices, sRAGE, and RAGE-related inflammatory genes expression after 10 weeks. Conclusion: Daily 125 mg DOE along with nutritional recommendations on top of usual care did not lead to significant changes in renal function indices, lipid profile, and inflammatory genes expression in patients with DN.